Modulatory antimicrobial activity of Piper arboretum extracts (Zingiberaceae) - Tintino, Saulo R.; Souza, Celestina E.S.; Guedes, Glaucia M.M.; Costa, Jacqueline I.V.; Duarte, Francisco M.; Chaves, Maria Celia O.; Silva, Viviane A.; Pessoa, Hillzeth L.; Lima, Micheline A.; Garcia, Carlos A.; Coutinho, Henrique (Acta Botanica Croatica, 2014)
The side effects of certain antibiotics have been a recent dilemma in the medical arena. Due this fact, the necessity of natural product discovery could provide important indications against several pharmacological targets and combat many infectious agents. Piper arboreum Aub. (Piperaceae) has been used by Brazilian traditional communities against several illnesses including rheumatism, bronchitis, sexually transmitted diseases and complaints of the urinary tract. Medicinal plants are a source of several remedies used in clinical practice to combat microbial infections. In this study, ethanol extract and fractions of Piper arboreum leaves were used to assay antimicrobial and modulatory activity. The minimum inhibitory concentration (MIC) was determined using microdilution method of ethanol extract and fractions from the leaves of P. arboreum ranging between 8 and 1024 mgmL–1. The capacity of these natural products to enhance the activity of antibiotic and antifungal drugs was also assayed. In these tests, natural products were combined with drugs. The natural products assayed did not demonstrate any clinically relevant antimicrobial activity (MIC ³ 1024 mg mL–1). However, the modulation of antibiotic activity assay observed a synergistic activity of natural products combined with antifungal (such as nystatin and amphotericin B) and antibiotic drugs (such as amikacin, gentamicin and kanamycin). According to these results, these natural products can be an interesting alternative not only to combat infectious diseases caused by bacteria or fungi, but also to combat enhanced resistance of microorganisms to antibiotic and antifungal drugs.